Pride and protectionism: U.S. trade policy and its impact on Asia - Zandi, Mark (Institutional Knowledge at Singapore Management University, 2018)
U.S. trade policy and its impact on Asia. Many of the trade policies of the United States President Donald Trump’s administration are aimed at addressing the perceived adverse impact of trade on the country’s manufacturing employment, and improving trade deals the President sees as not being in U.S. interests. These appear to be worthwhile goals, but crafting trade policy to address them is difficult.